Pengaruh Ritual Pengobatan Terhadap Intensitas Pemanfaatan Layanan Kesehatan Masyarakat - Husen, Bahrun Hi.; Muhdar, Kusrini; Muhammad, Sinta; Im, Supriadi (Peneliti.net, 2024)
Wonge is a healing ritual that is still often carried out by the people of Pulau Ternate District. The wonge ritual is carried out by interacting and asking for direct help from ancestral spirits to cure someone's illness. Most Ternate people believe that ancestral spirits can find the root of a person's illness, and can provide medicine in the form of mantras and water that has been prayed for as an antidote that can eliminate the illness. The wonge healing ritual is usually carried out on a large scale in November every year. The existence of the wonge ritual among the people of Pulau Ternate District seems to have an influence on the awareness of the people of Pulau Ternate District in utilizing first-level health services in the community, namely community health centers. Based on initial observations conducted at the two community health centers, there is an interesting fact that the data on the number of patient visits to the two community health centers from October to November experienced a decrease in visits of up to 30% from previous months. This is the initial conclusion that there is an influence of the wonge ritual on the utilization of health services at community health centers on Ternate Island. Thus, this is the main reason why researchers conduct further research. The purpose of this study is to describe the influence of wonge rituals on the intensity of health service utilization at the Community Health Centers on Ternate Island. The results of the study indicate that socio-cultural factors in the form of wonge healing rituals greatly influence the community in utilizing health services such as Community Health Centers